International handbook of social anxiety concepts, research and interventions relating to the self and shyness - Crozier, W. Ray; Alden, Lynn E. (John Wiley & Sons, 2001)
This handbook offers comprehensive coverage of current knowledge and recent advances with major sections on the origin and development of shyness and social anxiety, on social and personality factors, and on clinical perspectives and interventions. The editors have drawn together some of the worlds leading international experts from diverse disciplines offering a critical focus on knowledge that is research-based, central to the understanding of social anxiety, and of essential interest to a wide range of students, researchers and professionals.